SYSTEMATIZATION OF PHRASEOLOGICAL UNITS OF THE ENGLISH AND UZBEK LANGUAGES (Academia Science Repository, 2023)
This article deals with the analysis and systematization of phraseological units with the names of animals in the English and Uzbek languages, in a comparative plan and carried out semantic typology in two languages, taking into account the extralinguistic factors.